Microstructure predicts non-motor outcomes following deep brain stimulation in Parkinson’s disease - Philipp A. Loehrer; Miriam H. A. Bopp; Haidar S. Dafsari; Sieglinde Seltenreich; Susanne Knake; Christopher Nimsky; Lars Timmermann; David J. Pedrosa; Marcus Belke (npj Parkinson's Disease, 2024)
Abstract Deep brain stimulation of the subthalamic nucleus (STN-DBS) effectively treats motor and non-motor symptoms in advanced Parkinson’s disease (PD). As considerable interindividual variability of outcomes exists, neuroimaging-based biomarkers, including microstructural metrics, have been proposed to anticipate treatment response. In this prospective open-label study, we sought to detect microstructural properties of brain areas associated with short-term non-motor outcomes following STN-DBS. Thirty-seven PD patients underwent diffusion MRI and clinical assessments at preoperative baseline and 6-month follow-up. Whole brain voxel-wise analysis assessed associations between microstructural metrics and non-motor outcomes. Intact microstructure within specific areas, including the right insular cortex, right putamen, right cingulum, and bilateral corticospinal tract were associated with greater postoperative improvement of non-motor symptom burden. Furthermore, microstructural properties of distinct brain regions were associated with postoperative changes in sleep, attention/memory, urinary symptoms, and apathy. In conclusion, diffusion MRI could support preoperative patient counselling by identifying patients with above- or below-average non-motor responses.